2006
DOI: 10.1159/000093214
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Changes in Patients with Carotid Stenosis after Carotid Endarterectomy

Abstract: We investigated changes in neuropsychological function in patients with carotid stenosis following carotid endarterectomy (CEA) in relation to cerebral hemodynamics. The subjects were 24 patients who underwent CEA and 17 healthy controls matched by age, educational level, gender and handedness. Cerebral angiography, single-photon emission computed tomography (SPECT) and neuropsychological tests were performed approximately 1 week before and 3 weeks after CEA in all patients. In the patient group, the categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…14 Other studies have shown benefit from improved perfusion after carotid revascularization, particularly in patients with reduced cerebral reserve. 22,29,34,39 However, cognitive deterioration might also occur in the context of cerebral hyperperfusion. 14 From this literature review, it appears that there are more data supporting an effect from flow variation than from microembolism on cognitive performance after carotid revascularization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14 Other studies have shown benefit from improved perfusion after carotid revascularization, particularly in patients with reduced cerebral reserve. 22,29,34,39 However, cognitive deterioration might also occur in the context of cerebral hyperperfusion. 14 From this literature review, it appears that there are more data supporting an effect from flow variation than from microembolism on cognitive performance after carotid revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies analyzing flow modification by single photon emission CT found a correlation between flow modification and cognitive improvement in patients with reduced cerebral reserve. 29,34,39 The effect of microembolism was extensively analyzed but contradictorily defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the disadvantages of BMT, there is a downside to lack of repair: continued annual risk of stroke in excess of the annual risk after repair, psychologic effects of living with a threatening lesion, and the potential of long-term cognitive deterioration. [44][45][46][47][48] Drawing ridiculous conclusions from skimpy evidence, some have called for a cessation or severe limitation of carotid repair. 4,5,49 It is disingenuous to treat small groups of asymptomatic patients with nonlesions, see that they remain asymptomatic with BMT, and then claim victory.…”
Section: What Is the Evidence For Bmt Alone?mentioning
confidence: 99%